GE_GERICHTE C/14824/2012 vom 14. Oktober 2013 - GE Cour de justice (2013)
CONDITION DE RECEVABILITÉ; JONCTION DE CAUSES; SUSPENSION DE LA PROCÉDURE | Cst.29.1; Cst.29.2; CPC.319.B; CPC.124.1; CPC.126.1;